Ernest Sosa’s epistemology and other theories of knowledge - Pris, François-Igor E. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
We present the main traits of E. Sosa’s virtue (ability) epistemology, compare it with other approaches and highlight its strong and weak points. We focus on the problems of understanding of the nature and value of knowledge. In our view, Sosa’s approach suffers from a lack of the philosophy of language and an excess of metaphysics, which requires a Wittgensteinian «therapy». In this sense, T. Williamson’s «knowledge-first» epistemology is a more satisfactory and deep approach. Besides, we think, it allows for a Wittgensteinian interpretation and also the elaboration of a unified treatment of the approaches of E. Sosa, D. Pritchard, S. Goldberg and others.
Keywords: knowledge; nature of knowledge; value of knowledge; epistemic abilities/virtues; apt belief; safe belief; animal knowledge; reflective knowledge; full knowledge; epistemic achievement